A importância da controladoria no processo decisório da pequena empresa - Lorenzett, Daniel Benitti (2013)
The Comptroller is a management tool that helps and assists the entrepreneur in achieving organizational success, providing subsidies for the planning and control of business operations. In this context, the present study aimed to verify the presence of the Comptroller in the through academic and professional performing a survey of articles published in national journals in the past six years on the topic Controllership. Verified, too, with two groups of small businesses, how they use the information generated from the Comptroller in decision making. For the development of research was carried out a systematic analysis of the Comptroller theme through the portal of CAPES journals and a research survey, with two groups of companies served by SEBRAE / PR that occurred through the application of a questionnaire with open and closed. The results showed that the vast majority of articles published in Brazil about controllership are systematic review articles or bibliometric and that most of the companies studied do not have a department comptrollership installed and do not use the information available as aid in decision making. As a way to help companies studied in the understanding and implementation of a system for controllership was developed a simplified conceptual model and established a roadmap for its implementation. To reduce maintenance costs of the department controllership, the model developed works basically the integration of existing information in the organization for formulation of management decisions, a process that should be guided by a professional external to the organization, the personal controller, that should visit the company periodically, issue reports, analyze your financial situation and guide the decision making process.